Improve Sciences Learning Outcomes Using Animation Media in 5th Grade Elementary School Students - Krisanti, Evantina (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve student learning outcomes in science muple grade V elementary schools with animated media assisted by google meet. The research conducted was a Classroom Action Research (PTK) in three cycles, with each cycle consisting of one meeting. The stages of each cycle are planning, implementing, observing, evaluating, and reflecting. At each meeting, an evaluation is carried out to find out the development of students. In the first cycle, the students' average score was 74.61. In the second cycle, the students' average score was 91.53. In the third cycle, the average value of students was 96.92. These results indicate that animation media can improve student learning outcomes, especially science muple class V at SDN Ketitang Wetan 01.